2020
DOI: 10.1371/journal.pone.0227314
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of NK cells in Mexican pediatric patients with acute lymphoblastic leukemia: Report from the Mexican Interinstitutional Group for the Identification of the Causes of Childhood Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children around the globe. Mexico City has one of the highest incidence rates of childhood leukemia worldwide with 49.5 cases per million children under the age of 15 which is similar to that reported for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…The conditioning regimen and intensity, prior treatment regimens, prior recipient of cellular and immunotherapy, the interval between last treatment and CAR-T, as well as disease status at the time of CAR-T also contribute to the cumulative risk of infection after CAR-T. For instance, the duration and depth of neutropenia determine overall infection risk in patients receiving multi-agent cytotoxic chemotherapy, such as in acute leukemia and lymphoma. Further, NK and T-cell mediated cytotoxicity is impaired with patients with ALL and worse in patients with T-ALL compared to B-ALL 105 . Patients with chronic lymphocytic leukemia (CLL) and MM have an inherent predisposition to infections associated with hypogammaglobulinemia and compromised humoral immunity 106 , 107 , 108 .…”
Section: Infection Risks In Patients With Car-t Immunotherapymentioning
confidence: 98%
“…The conditioning regimen and intensity, prior treatment regimens, prior recipient of cellular and immunotherapy, the interval between last treatment and CAR-T, as well as disease status at the time of CAR-T also contribute to the cumulative risk of infection after CAR-T. For instance, the duration and depth of neutropenia determine overall infection risk in patients receiving multi-agent cytotoxic chemotherapy, such as in acute leukemia and lymphoma. Further, NK and T-cell mediated cytotoxicity is impaired with patients with ALL and worse in patients with T-ALL compared to B-ALL 105 . Patients with chronic lymphocytic leukemia (CLL) and MM have an inherent predisposition to infections associated with hypogammaglobulinemia and compromised humoral immunity 106 , 107 , 108 .…”
Section: Infection Risks In Patients With Car-t Immunotherapymentioning
confidence: 98%
“…Already in 1989, Gabrilovac et al observed impairment of NK cell function in ALL [122]. More recent studies confirmed alterations in the phenotype and cytotoxicity of NK cells derived from ALL patients [118,121]. As compared to healthy donors, NK cells from pediatric ALL patients had lower levels of NKp46 activating receptors and higher levels of inhibitory NKG2A receptors [118].…”
Section: Alterations In the Numbers And Activity Of Nk Cellsmentioning
confidence: 99%
“…Early studies showed that patients suffering from ALL have abnormal percentages and absolute numbers of NK cells [120]. Moreover, Valenzuela-Vazquez et al confirmed these observations in Hispanic ALL patients, especially in those diagnosed with T-ALL [121]. Already in 1989, Gabrilovac et al observed impairment of NK cell function in ALL [122].…”
Section: Alterations In the Numbers And Activity Of Nk Cellsmentioning
confidence: 99%
“…Indeed, NK cell abnormality or de ciency is a risk factor for CMV reactivation [46]. This condition could explain the occurrence of elevated CMV reactivation among patients with ALL described in this study and elsewhere, once NK cell abnormalities were already reported in these patients [47]. In this study, we did not assess the phenotype of NK cells in patients positive for CMV IgM to verify this correlation.…”
Section: Discussionmentioning
confidence: 78%